The effectiveness of technology transfers among rubber smallholders in Terengganu - Abdul Malik Ismail
Low level of technology adoption and land productivity in rubber smallholder sector were often associated with ineffective of Transfer of Technology (TOT) programmes that target them. This study assesses the effectiveness of Transfer of Technology (TOT) programmes among the rubber smallholders who have mature rubber trees in Terengganu. Data were collected using questionnaires by conducting face to face interviews with 200 rubber smallholders from seven districts of Terengganu namely Kuala Terengganu, Marang, Besut, Setiu, Hulu Terengganu, Dungun and Kemaman. The gathered data was analysed using SPSS software. The results of the study identified demonstration and field visits as the most effective programmes in the TOT for group and individual categories. It was also found that the effective of TOT programmes and involvement in TOT programmes had strong and positive correlations with the understanding about technologies. The standardized regression coefficient (beta) for understanding score was .345 (t=89.525, p<0.001), which revealed that the understanding has the strongest and contributed the most to the effectiveness of the TOT programme. The study also found that 42.5% of the respondents' incomes from rubber production are small due to their small farm size, less number of tapping days and not adopting technologies in their farm. These findings could be used by relevant authorities and organizations to plan more comprehensive and strategic programmes in technology transfer activities to rubber smallholders, particularly to increase their income up to RM3800 a month as envisage under NKEA for High Income Nation. With proper planning and policies this aim will be realised for the benefit of the rubber smallholders.